A mutação constitucional da suspensão senatorial à luz do sistema brasileiro de precedentes - COSTA FILHO, César Pereira da (Universidade Federal do Oeste do Pará, 2024)
The approach regarding the constitutional mutation of the article 52, X, of the Federal Constitution of Brazil comes up with elements of a much deeper discussion about the contemporary constitutional law field. Using the hypothetical-deductive methodology, the main objective is to re-read both the mentioned new-interpretation of the article 52, X and the Federal Senate's suspension of law enforcement itself - in other words, a re-reading process that must always be done by considering the current context of the national legal system, the democratic State of law and the judicial review. In this discussion, it was necessary to go through concepts and different points of view regarding the constitutional mutation, given the fact it is the main subject of this paper.Therefore, it is more than a purely formalistic discussion. Concludes that the diffuse-control of constitutionality (constitutional judicial review) is presented as one of the instruments of effectiveness of the Constitution.